Synthesis, structures and reactivity of group 4 hydrazido complexes supported by calix[4]arene ligands. - Clulow, A; Selby, J; Cushion, MG; Schwarz, A; Mountford, P (2008)
Reaction of TiCl(2)(Me(2)Calix) with 2 equiv of LiNHNRR' afforded the corresponding terminal hydrazido(2-) complexes Ti(NNRR')(Me(2)Calix) (R = Ph, R' = Ph (1) or Me; R = R' = Me (3)) which were all structurally characterized. The X-ray structure of Ph(2)NNH(2) is reported for comparison. Compound 1 was also prepared from Na(2)[Me(2)Calix] and Ti(NNPh(2))Cl(2)(py)(3). Reaction of ZrCl(2)(Me(2)Calix) with 2 equiv of LiNHNR(2) afforded only the bis(hydrazido(1-)) complexes Zr(NHNR(2))(2)(Me(2)Calix) (R = Ph or Me). Treatment of Ti(NNMe(2))(Me(2)Calix) (3) with MeI gave the zwitterionic hydrazidium species Ti(NNMe(3))(MeCalix) (6) via a net isomerization reaction which was found to be catalytic in MeI. The corresponding reaction of 3 with CD(3)I gave Ti(NNMe(2)CD(3))(MeCalix) (6-d(3)) with concomitant elimination of MeI. Reaction of 3 with 1 equiv of MeOTf gave [Ti(NNMe(3))(Me(2)Calix)][OTf] (7-OTf) which in turn reacted with (n)Bu(4)NI to form 6 and MeI. Addition of PhCHO to 3 gave the mu-oxo dimer [Ti(mu-O)(Me(2)Calix)](2) and benzaldehyde-dimethylhydrazone. Reaction of either 3 or 6 with (t)BuNCO gave the zwitterionic species Ti{(t)BuNC(NNMe(3))O}(MeCalix) (10) which has been crystallographically characterized. Compound 10 is the formal product of insertion of an isocyanate into the Ti=N(alpha) bond of a titanium hydrazide or hydrazidium species (Me(2)Calix or MeCalix = dianion or trianion of the di- or monomethyl ether of p-tert-butyl calix[4]arene, respectively).